2021
DOI: 10.1186/s12872-021-02146-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate biomarkers and therapeutic agents for heart failure by bioinformatics analysis

Abstract: Introduction Heart failure (HF) is a heterogeneous clinical syndrome and affects millions of people all over the world. HF occurs when the cardiac overload and injury, which is a worldwide complaint. The aim of this study was to screen and verify hub genes involved in developmental HF as well as to explore active drug molecules. Methods The expression profiling by high throughput sequencing of GSE141910 dataset was downloaded from the Gene Expressi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 187 publications
(175 reference statements)
4
24
0
Order By: Relevance
“…In cardiomyopathy, alternative splicing has been shown to target calcium signalling, sarcomere organisation and apoptosis ( Hu et al, 2017 ; Dlamini et al, 2015 ; Kong et al, 2010 ). These findings are in keeping with our data indicating that splicing-induced functional changes in proteins are important for regulating cardiac muscle architecture ( Kolur et al, 2021 ; D'Amario et al, 2018 ), calcium homeostasis ( Torac et al, 2014 ; Wanitchakool et al, 2017 ), inflammation ( Comerford et al, 2006 ; Wu et al, 2019 ; Morgan and Harris, 2015 ) and circadian rhythmicity ( Young, 2006 ; Wang et al, 2021 ). The numerous changes in response to sActRIIB treatment are likely due to signalling changes downstream of the activin receptor.…”
Section: Discussionsupporting
confidence: 92%
“…In cardiomyopathy, alternative splicing has been shown to target calcium signalling, sarcomere organisation and apoptosis ( Hu et al, 2017 ; Dlamini et al, 2015 ; Kong et al, 2010 ). These findings are in keeping with our data indicating that splicing-induced functional changes in proteins are important for regulating cardiac muscle architecture ( Kolur et al, 2021 ; D'Amario et al, 2018 ), calcium homeostasis ( Torac et al, 2014 ; Wanitchakool et al, 2017 ), inflammation ( Comerford et al, 2006 ; Wu et al, 2019 ; Morgan and Harris, 2015 ) and circadian rhythmicity ( Young, 2006 ; Wang et al, 2021 ). The numerous changes in response to sActRIIB treatment are likely due to signalling changes downstream of the activin receptor.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, clinical evidence revealed that CCDC80 expression was significantly increased in patients with pulmonary arterial hypertension and heart failure. 40 , 41 , 42 This evidence indicates a close association between CCDC80 and cardiovascular system.…”
Section: Resultsmentioning
confidence: 67%
“…The LV free‐wall tissues were harvested at the time of cardiac surgery from subjects with heart failure undergoing transplantation and from unused donor hearts with apparently normal function. The expression matrix was reserved in the gene expression omnibus (GEO) database (https://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE141910), 34 and the clinical characteristics of involved samples in GSE141910 were listed in Table . In addition, the validation of autophagy model was performed in another microarray dataset GSE57338 (https://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE57338).…”
Section: Methodsmentioning
confidence: 99%
“…The expression matrix was reserved in the gene expression omnibus (GEO) database (https://www.ncbi.nlm.nih.gov/geo/query/ acc. cgi?acc=GSE14 1910), 34 and the clinical characteristics of involved samples in GSE141910 were listed in Table S1. In addition, the validation of autophagy model was performed in another microarray dataset GSE57338 (https://www.ncbi.nlm.nih.gov/geo/query/ acc.cgi?acc=GSE57338).…”
Section: Data Preprocessmentioning
confidence: 99%